ELEMENTS OF THE BLACK CURRANT PRODUCTIVITY COMPONENT IN THE ENVIRONMENTS OF THE RUSSIAN NORTH-WEST - O. A. Tikhonova (Труды по прикладной ботанике, генетике и селекции)
In this article the results of evaluating of potential and actual productivity of 39 black currant varieties are given. The sources of important components of productivity for using in breeding programs were revealed. The best cultivars that can realize their highest potential possibilities in the North-West of Russia were identified. Correlations between the potential productivity and its individual components were detected.